Effects of Ni-doping on the photo-catalytic activity of TiO2 anatase and rutile: Simulation and experiment. (September 2018) - Elahifard, Mohammad Reza; Ahmadvand, Seyedsaeid; Mirzanejad, Amir
Abstract: The Ni impurity has an inconsistent impact on the photo-catalytic activity of TiO2 in different regions of electromagnetic radiation. In this work, the effect of different concentrations of Ni doping into anatase and rutile TiO2 structures is investigated theoretically and experimentally. Doubling the concentration of doped Ni does not change the photo-catalytic activity of TiO2 significantly according to photo-degradation of Acid Blue 92 (AB 92) under ultra violate and visible (UV–Vis) lights. However, increment of the dopant concentration enhances the thermodynamic yield of TiO2 crystalline structure (i.e. rutile) at low temperature calcination of TiO2 . Density functional theory (DFT) calculations also confirm the impact of Ni impurity on the higher stability of rutile phase. Computational geometry optimization favors a heterogeneous distribution of Ni atoms in 12.5 at% Ni-TiO2, that is verified by a broad impurity peak inside the band gap of TiO2 in UV–Vis diffuse reflectance spectrum (UV–Vis DRS). The DRS and DFT results denote a negligible change in the band gap energy of TiO2 compared to Ni-TiO2 . Based on DFT results, generation of defect states gives rise to photo-catalytic activities of Ni-TiO2 in the invisible region. However, adding Ni to anatase TiO2 changes the type of the band gap from indirect to direct and reduces its photo-efficiency in the degradation of AB 92 under UV irradiation. In addition, a positive shift of the valance and conduction band edges of TiO2 occurs after Ni doping, which reduces the photo-oxidation activity of TiO2 .